(untitled) (Bangladesh Pharmaceutical Journal, 2015)
In the present work, three methods were used to inverse chitosan swelling behavior including, conjugation of p-amino benzoic acid (PABA) on cross-linked chitosan in different condition, Michael addition reaction of acrylic acid (AA) on chitosan and finally graft copolymerization of methacrylic acid (MMA) on chitosan. We couldnt inverse chitosan swelling behavior by the Michael addition reaction of acrylic acid, but conjugation of PABA on cross-linked chitosan inversed the chitosan swelling behavior. In addition, the graft copolymerization of MMA on chitosan was also successful. In general, the third method, among the above-mentioned modifications provided the best results. Bangladesh Pharmaceutical Journal 18(2): 110-117, 2015